Cybersecurity : key legal considerations for the aviation and space sectors - Bergamasco, Federico (Aerospace law and policy series ;, 2020)
Cybersecurity' is a resourceful book which explores the current laws relevant to aviation and space cybersecurity and analyses them from a critical perspective. The growing connection between the aviation and space sectors and reliance on related technology make them more susceptible to potential cyberattacks. Consequently, cybersecurity is becoming a pressing concern that should be taken into consideration by stakeholders in both sectors. This progressive book takes an introductory approach to allow those unfamiliar with aviation and space law, including telecommunications, and/or cybersecurity to gain valuable insight into these areas, and the subsequent chapters delve deep into the gamut of relevant international and European Union (EU) laws, with specific attention to associated risks, existing legal provisions and the potential development of new rules.